What Is Nuclear Factor Kappa B (NF-κB) Doing in and to the Mitochondrion? - Albensi, Benedict C. (Frontiers in Cell and Developmental Biology, 2019)
A large body of literature supports the idea that nuclear factor kappa B (NF-kB) signaling contributes to a network hub controlling not only immunity, but also inflammation, cancer, and nervous system function. However, studies on NF-kB activity in mitochondrial function are much more limited and scattered throughout the literature. Upon further thought this is very surprising given the importance and the evolutionary history of both NF-kB and the mitochondrion. Both are ancient in their appearance in our biological record where both contribute substantially to cell survival, cell death, and the regulation of function and/or disease. In this review, an attempt is made to understand how NF-kB activity precisely contributes to mitochondrial function. It is assumed the reader already has an understanding of basic mitochondrial biology. The discussion at times is speculative and lacking in evidence, and perhaps even provocative to some, since NF-kB does not yet have defined mitochondrial targeting sequences for some nuclear-encoded mitochondrial genes and mechanisms of mitochondrial import for NF-kB are not yet entirely understood. However, the overall question is legitimate – What is NF-kB doing in the mitochondrion?